Improving CT quality with optimized image parameters for radiation treatment planning and delivery guidance. (October 2017) - Chen, Guang-Pei; Noid, George; Tai, An; Liu, Feng; Lawton, Colleen; Erickson, Beth; Li, X. Allen
Abstract: Background and purpose: CT scan protocols are often created with imaging parameters set to minimize imaging dose with acceptable image quality for diagnostic purpose. This study aimed to optimize CT imaging parameters to help accurately delineate structures for radiation therapy planning and delivery guidance. Materials and methods: Imaging parameters were optimized with CT data acquired for a phantom to create image quality enhancement (IQE) protocols, which were subsequently used to scan a prostate and a pancreatic cancer patient who underwent image-guided radiotherapy (IGRT). The patient images were compared with those scanned with standard clinical protocols, the quality of these images was assessed with various methods (survey, inter- and intra-observer variations, and dice coefficient analysis) for the two patient cases. Results: An effective tube current–time product of ∼1000 mAs was found to be a reasonable choice to balance CT quality and CT dose. With increased dose and penetration taken into account, 100 and 120 kV tube voltages were found appropriate for the IQE protocols. The inter- and intra-observer variations for the IQE data were smaller than those with the standard protocols. Dice coefficient analysis indicated that the IQE protocols lead to improved dice coefficient by as much as 8 percentage points for the two cases studied. Conclusion: CT image quality can be improved with the IQE protocols created in this study, to provide better soft tissue contrast, which would be beneficial for use in radiation therapy, e.g., for planning data acquisition or for IGRT for hypo-fractionated treatments.